2010
DOI: 10.1590/s0036-46652010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect (in vitro) of Moringa oleifera and Annona muricata against Gram positive and Gram negative bacteria

Abstract: SUMMARYAntibacterial effects of aqueous and ethanolic extracts of seeds of moringa (Moringa oleifera) and pods of soursop (Annona muricata) in the concentration of 1:5 and 1:10 in volumes 50, 100, 150 and 200 μL were examined against Staphylococcus aureus, Vibrio cholerae, Escherichia coli (isolated from the organism and the aquatic environment) and Salmonella Enteritidis. Antibacterial activity (inhibition halo > 13 mm) against S. aureus, V. cholerae and E. coli isolated from the whiteleg shrimp, Litopenaeus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 33 publications
3
93
0
8
Order By: Relevance
“…All parts of Annona muricata are extensively used as traditional medicines against an array of human ailments and diseases. Previous reports on Annona muricata reveal it possesses anti-oxidant effect Baskar [10] anti-proliferative effect [11,12] and anti-trypanosomal effects [13], anti-bacterial effect [14,15], anti-hepatotoxic activity [16,17], wound healing activity [18]. The antinociceptive and anti-inflammatory effect of the ethanol extract of the plant in animal models has also been reported [19][20][21].…”
Section: Determination Of the Effect Of The Extract On Phospholipase mentioning
confidence: 99%
“…All parts of Annona muricata are extensively used as traditional medicines against an array of human ailments and diseases. Previous reports on Annona muricata reveal it possesses anti-oxidant effect Baskar [10] anti-proliferative effect [11,12] and anti-trypanosomal effects [13], anti-bacterial effect [14,15], anti-hepatotoxic activity [16,17], wound healing activity [18]. The antinociceptive and anti-inflammatory effect of the ethanol extract of the plant in animal models has also been reported [19][20][21].…”
Section: Determination Of the Effect Of The Extract On Phospholipase mentioning
confidence: 99%
“…Moringa oleifera was also shown to inhibit pathogenic bacteriathatcan affect marine aquaculture products [27]. Brihanteet al [28] showed that the ethanol extract of Moringa oleifera pods and chloroform extract of flowers could effectively inhibit three strains of Vibrio cholera, Vibrio vulnificus and Vibrio mimicus isolated from Macrobrchium amazonicum prawns.…”
Section: Antibacterial Activities Of Moringa Oleiferamentioning
confidence: 99%
“…Abortifacient Leaves, roots [113], [114] Against Plasmodium falciparum and Schistosoma mansoni cercariae Seeds [105], [106] Analgesic Roots [27], [84] Antiatherosclerotic Leaves [69] Anticlastogenic Leaves, pods [63], [64] Anti-constipant Flowers [109] Anticonvulsant Leaves, roots [27], [103], [104] Antiespasmodic Leaves, seeds [80] Antihelminthic Seeds [53] Anti-inflammatory Seeds, leaves, roots [80], [81], [82], [83] Antioxidant Leaves, seeds [24], [25], [26], [63], [67], [68], [70] Antipyretic Leaves [18] Antitumor Seeds, stem, leaves [68], [72], [87], [88] Antiulcerogenic Leaves, seeds [65], [66] Bactericidal Leaves, stem, pods [17], [93], [97], [94], [95], [96] Bradycardic/Hipotensive Seeds [77], [78], [79] Diuretic Seeds [80] Fungicide Leaves, seeds [91], …”
Section: Part Of Plant Referencementioning
confidence: 99%